2011
DOI: 10.1002/jbm.b.31907
|View full text |Cite
|
Sign up to set email alerts
|

Degradation‐induced changes of mechanical properties of an electro‐spun polyester‐urethane scaffold for soft tissue regeneration

Abstract: The aim of this study was the in vitro investigation of the change in mechanical properties of a fast-degrading electro-spun polymeric scaffold for the use in soft tissue regenerative implants. Tubular scaffolds were electro-spun from a DegraPol® D30 polyesther-urethane solution (target outer diameter: 5.0 mm; scaffold wall thickness: 0.99 ± 0.18 mm). Scaffold samples were subjected to hydrolytic in vitro degradation for up to 34 days. The fiber network structure and fiber surfaces were inspected on scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…Consistent with earlier results (Krynauw et al, 2011), fibre fracture and pitting were not apparent during degradation period of up to 28 days. The SEM images showed an increase in the surface roughness of the fibres during degradation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with earlier results (Krynauw et al, 2011), fibre fracture and pitting were not apparent during degradation period of up to 28 days. The SEM images showed an increase in the surface roughness of the fibres during degradation.…”
Section: Discussionsupporting
confidence: 92%
“…The goodness of fit between the theoretical and experimental stress is assessed using the correlation coefficient. In an earlier study it was found that degradation did not affect electrospun fibre orientation (Krynauw et al, 2011). Consequently, the parameter ߩ controlling the degree of anisotropy which was determined for the non-degraded sample was fixed (ߩ = 1.27013) for the other identification procedures (time = 4 to 28 days).…”
Section: Constitutive Identification Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyesters are created de novo , no animal material has to be used to synthesize them. They can be combined with other compounds and it is possible to control their shape, size, porosity, cell attachment, or biodegradability [19][21]. Disadvantages are possibility of inflammation inducted by a too long degradation time for PLCL [22], [23].…”
Section: Introductionmentioning
confidence: 99%